Diagnostic Value of Urinary CD80 in Typical and Atypical Nephrotic Syndrome (Bangladesh Journal of Child Health, 2024)
Background: Cluster of differentiation 80 is one of the important biomarker which is present on podocytes. Urinary CD80 concentration increases only in patients with typical nephrotic syndrome in active state and level remains normal in patients with atypical nephrotic syndrome. Objective: To evaluate urinary CD80 concentration as a diagnostic marker of typical and atypical nephrotic syndrome. Methods: This was a cross sectional study, performed in the Department of Paediatrics & Paediatric Nephrology, Chittagong Medical College Hospital, Chattogram. Thirty nine with typical and 36 with atypical nephrotic syndrome were enrolled from January 2020 to July 2021.Urinary CD80 concentration was measured and compared between typical and atypical nephrotic syndrome. Results: Mean urinary CD80 concentration in typical nephrotic syndrome (671.92 ±328.45) was found significantly higher (p